The Implementation of Muhammad Abduh's Thought in Islamic Education in the Era of Globalization - Yoyoh Badriyyah; Nurlaila Turohmah; Darrotul Jannah; Moh. Al Haidar (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2025)
This study explores the implementation of Muhammad Abduh’s educational thought in the context of Islamic education during the era of globalization. Abduh, as one of the prominent Muslim reformers, emphasized the integration of religious sciences with modern knowledge, rejecting the dichotomy between Islamic education and general education. Using a qualitative library research method, this article analyzes Abduh’s intellectual legacy and its relevance to contemporary challenges in Islamic education, such as technological advancement, unresponsive curricula, and incompetent educators. The findings highlight that Abduh’s ideas on curriculum adjustment, critical and active learning methodologies, and universal access to education provide significant solutions to current educational problems. His vision underlines the necessity of balancing religious and secular knowledge to produce students who are not only intellectually capable but also morally grounded. The study concludes that revitalizing Abduh’s thought is crucial for the sustainability and competitiveness of Islamic education in the modern global era.